The Influence of Digital Economy Development on Post Covid-19 Pandemic Economic Growth in Indoneia - Amalia Syaputri; Khusnul Fatimah; Septiani Bela Kusumaningtyas (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2023)
The purpose of this study is to determine the effect of the digital economy on economic growth after the Covid-19 pandemic. This research method uses a quantitative descriptive method to examine theories and measure the influence of digital economic development on economic growth, using the classical assumption test and simple linear regression analysis. The data used is secondary data sourced from the Central Statistics Agency (BPS), internet searches, journals, and other sources related to the digital economy and economic growth in Indonesia. The results of the study show that the projected digital economy with IP-TIK has no significant effect on post-Covid-19 economic growth in Indonesia.